High-latitude teleconnections drive subtropical marine bioproductivity at the dawn of the Antarctic ice sheet - Alexandra Villa; Stephen R. Meyers (Proceedings of the National Academy of Sciences, 2026)
The inception of the Antarctic ice sheet (AIS) marked a major global climatic reorganization of the Cenozoic, but the response of the subtropical marine biosphere remains poorly constrained. A new sediment archive from the subtropical South Atlantic (IODP Exp. 390 and 393) reveals a sevenfold increase in surface ocean bioproductivity proxy accumulation (biogenic barium) commensurate with the initial expansion of the AIS 34 Mya, and the emergence of an amplified astronomical forcing of subtropical bioproductivity that mirrors the subsequent evolution of the AIS in the early Oligocene. We find that a strong 40-kyr obliquity response characterizes subtropical bioproductivity following the initial establishment of an expansive marine-based AIS. Portions of the AIS in contact with the marine environment are sensitive to meridional heat delivery controlled by obliquity-forced interactions between the atmosphere and ocean, which can propagate to the lower latitudes via Southern Ocean overturning circulation. The surprising emergence of obliquity forcing of low-latitude bioproductivity enhances our understanding of global teleconnections and feedbacks that regulate global climate, and points to mechanisms driving global marine bioproductivity on astronomical timescales—and their intricate connections to the evolution of the cryosphere.